CONCEPT OF PROSECUTORIAL SUPERVISION ON THE INVESTIGATION OF CRIMES FOR THE LEGALIZATION OF INCOME DERIVED FROM CRIMINAL ACTIVITY, THE SCIENTIFIC AND THEORETICAL FOUNDATIONS OF ITS SUBJECT AND OBJECT (World Bulletin of Management and Law, 2025)
The article presents the scientific-theoretical foundations of the concept, subject, and object of prosecutor’s supervision over the investigation of crimes related to the legalization of proceeds from criminal activities. The theoretical views of scholars who conducted scientific research are analyzed, and the relevance of prosecutor's supervision in the initial stages of investigation into these types of crimes is discussed. Scientific concepts regarding the concept, subject, and object of prosecutor’s supervision are provided.
Keywords: crimes related to the legalization of proceeds from criminal activities; investigative and initial investigation authorities; prosecutor’s supervision